2022
DOI: 10.1186/s12935-022-02519-9
|View full text |Cite
|
Sign up to set email alerts
|

HOXA7 promotes the metastasis of KRAS mutant colorectal cancer by regulating myeloid-derived suppressor cells

Abstract: Background KRAS mutation accounts for 30–50% of human colorectal cancer (CRC) cases. Due to the scarcity of effective treatment options, KRAS mutant CRC is difficult to treat in the clinic. Metastasis is still the major cause of the high mortality associated with KRAS mutant CRC, but the exact mechanism remains unclear. Here, we report a unique function of Homeobox 7 (HOXA7) in driving KRAS mutant CRC metastasis and explore therapeutic strategies for subpopulations of patients with this disease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
2
5
0
1
Order By: Relevance
“…HOXA7 has been reported to be responsible for upregulating chemokines to draw myeloid-derived immune suppressive cells into the TME. 29 Consistently, our results found that HOXA7 recruits TAMs through upregulation of CCL2, which has been reported to shape macrophage polarization under the influence of macrophage colony-stimulating factor 34 and promotes TAM recruitment through its receptor CCR2. 35 Our results showed that knockdown of HOXA7 significantly attenuated CCL2 secretion instead of other CCLs, thus inhibiting TAM infiltration and polarization.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…HOXA7 has been reported to be responsible for upregulating chemokines to draw myeloid-derived immune suppressive cells into the TME. 29 Consistently, our results found that HOXA7 recruits TAMs through upregulation of CCL2, which has been reported to shape macrophage polarization under the influence of macrophage colony-stimulating factor 34 and promotes TAM recruitment through its receptor CCR2. 35 Our results showed that knockdown of HOXA7 significantly attenuated CCL2 secretion instead of other CCLs, thus inhibiting TAM infiltration and polarization.…”
Section: Discussionsupporting
confidence: 89%
“…Tumor‐associated macrophages exert immunosuppressive effects on tumor‐infiltrating lymphocytes and secrete anti‐inflammatory cytokines and chemokines including Arg1, 31 interleukin‐10, 32 and TGF‐β, 33 which strongly contribute to tumor proliferation and migration. HOXA7 has been reported to be responsible for upregulating chemokines to draw myeloid‐derived immune suppressive cells into the TME 29 . Consistently, our results found that HOXA7 recruits TAMs through upregulation of CCL2, which has been reported to shape macrophage polarization under the influence of macrophage colony‐stimulating factor 34 and promotes TAM recruitment through its receptor CCR2 35 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Constitutive-activated KRAS mutation results from a point mutation most commonly seen in codons 12 and 13 in CRC, increasing the risk of cancer development and causing cancer cells, if formed, to proliferate uncontrollably and metastasize in the body [ 7 ]. It is estimated that 30-50% of CRC patients harbor the mutated KRAS gene form [ 8 ]. These mutations are strongly associated with resistance to anti-EGFR therapy, such as cetuximab and panitumumab.…”
Section: Introductionmentioning
confidence: 99%
“…The downregulated expression of HOXA7 in ccRCC and its lower expression being associated with poorer patients' prognosis indicated that it might be a tumor suppressor in ccRCC. However, HOXA7 was recently more reported to be oncogene and promoted oncogenic characteristics in many kinds of tumors such as liver cancer, cervical cancer, ovarian cancer, colorectal cancer and breast cancer (65)(66)(67)(68)(69). The role of HOXA7 in ccRCC had not been reported until now and exploring its effect on malignant characteristics of ccRCC might lead to the understanding of its diverse biological role and the complicated intracellular regulatory network.…”
Section: Discussionmentioning
confidence: 99%